2009
DOI: 10.1007/s11096-009-9352-6
|View full text |Cite
|
Sign up to set email alerts
|

Electronic screening of medical records to detect inpatients at risk of drug-related problems

Abstract: This tool allows for efficient and rapid screening of patients at risk of DRPs in preparation for the ward round. It helps CPs to prioritize their medication reviews and to optimize their workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 17 publications
(14 reference statements)
6
62
2
Order By: Relevance
“…The percentage of in‐hospital patients experiencing a DRP in our study was similar to that reported by other authors who identified 33 DRP per 100 in‐hospital patients, with a mean of 1.71 DRP per patient in those with DRP . Much higher figures for DRP have been reported, ranging between 64.7% and 81.3%, although these figures are drawn from analyses of a small number of medical departments and included patients with comorbidities that could explain these values. In these studies, the rate of DRP per patient was between 3.17 and 6.5 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The percentage of in‐hospital patients experiencing a DRP in our study was similar to that reported by other authors who identified 33 DRP per 100 in‐hospital patients, with a mean of 1.71 DRP per patient in those with DRP . Much higher figures for DRP have been reported, ranging between 64.7% and 81.3%, although these figures are drawn from analyses of a small number of medical departments and included patients with comorbidities that could explain these values. In these studies, the rate of DRP per patient was between 3.17 and 6.5 .…”
Section: Discussionsupporting
confidence: 89%
“…Computerized physician order entry (CPOE) systems have recently become available, and their application in the daily monitoring of the drug therapy of in-hospital patients can help to detect DRP and identify their possible causes. 12,13 Certain clinical and/or demographic characteristics, nevertheless, can increase the risk of DRP in some hospitalized patients, requiring closer monitoring of pharmacological therapy. Consequently, the aim of this study was to design a risk score to identify DRP-prone in-hospital patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it may possible to describe drug use patterns, analyze early signals of the irrational drug use, promote interventions to improve drug use, analyze quality control cycles, and promote continuous quality improvement (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Previous research has identified medicines that are potentially high‐risk when used in a hospital inpatient setting, but no statistical assessment of high‐risk medicines and clinically relevant medication‐related problems (MRPs) has yet been conducted. Statistical assessment has potential to quantify the impact of groups of high‐risk medicines on the risk of developing clinically relevant MRPs, and to explore potential correlation between high‐risk medicines and other risk factors such as age and renal function.…”
Section: Introductionmentioning
confidence: 99%